2015
DOI: 10.17576/jsm-2015-4409-10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Cryoprotectants and Sperm Densities of Orange Mud Crab, Scylla olivacea (Herbst, 1796) for Long-Term Storage of Spermatozoa

Abstract: The objectives of this study were to determine the effect of different cryoprotectants and sperm densities for longterm storage of orange mud crab, Scylla olivacea spermatozoa. Spermatozoa were obtained by homogenizing the spermatophores using a glass homogenizer in an ice-bath followed by centrifugation at 4°C. Spermatozoa were then suspended in calcium-free saline (Ca-F saline)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…The ndings of the sperm mass features in this study were similar to those described previously in S. olivacea (Noorbaiduri et al 2014;Ikhwanuddin et al 2015). The concentration in this study was slightly lower than that previous reported, which was 2.6-3.0 × 10 9 sperm/mL (Ikhwanuddin et al 2015).…”
Section: Lm and Tem Observationsupporting
confidence: 89%
See 2 more Smart Citations
“…The ndings of the sperm mass features in this study were similar to those described previously in S. olivacea (Noorbaiduri et al 2014;Ikhwanuddin et al 2015). The concentration in this study was slightly lower than that previous reported, which was 2.6-3.0 × 10 9 sperm/mL (Ikhwanuddin et al 2015).…”
Section: Lm and Tem Observationsupporting
confidence: 89%
“…The ndings of the sperm mass features in this study were similar to those described previously in S. olivacea (Noorbaiduri et al 2014;Ikhwanuddin et al 2015). The concentration in this study was slightly lower than that previous reported, which was 2.6-3.0 × 10 9 sperm/mL (Ikhwanuddin et al 2015). This is probably due to the difference in the method of sperm preparation, such as dilution factor, or the size and geographical difference of the crab samples.…”
Section: Lm and Tem Observationsupporting
confidence: 88%
See 1 more Smart Citation
“…Photos of eggs were taken with a smartphone and the eggs were counted over photos. Fertilized eggs were separated based on the different coloring of unfertilized eggs (Ikhwanuddin et al 2015). The diameters of eggs were measured with a micrometer using a microscope.…”
Section: Reproductive Performancementioning
confidence: 99%
“…High-quality diets decrease crab mortality, resulting in greater sperm production. Excess sperm can then be cryopreserved for future use in artificial insemination (Ikhwanuddin et al 2015c). In this study, we aimed to evaluate the effects of a squid (Loligo sp.)…”
Section: Introductionmentioning
confidence: 99%